Sosialisasi Pencegahan Stunting Di Desa Tanggo Raso Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Gusni Rahmarianti; Parwito Parwito (JURNAL PENGABDIAN KESEHATAN, 2023)
Stunting is a condition of growth failure in children under five years of age due to chronic malnutrition so children become too short for their age. This activity aims to increase the knowledge of mothers who have toddlers about preventing stunting in Tanggo Raso Village, Pino Raya District, South Bengkulu Regency. The method used in this service is a lecture (presentation) and weighing of toddlers to determine the condition of children's growth and development. This counseling activity was followed by participants with great enthusiasm, as seen from the participants who participated in the activities carried out. This activity provides additional knowledge about stunting to mothers who have toddlers and pregnant women in Tanggo Raso Village, Pino Raya District, South Bengkulu Regency. It is hoped that after this counseling activity, the community can apply the knowledge gained in their daily lives, and there is a need for continued assistance by the service team and the local puskesmas through posyandu activities so that efforts to prevent stunting can be realized.